2022
DOI: 10.1136/bmjopen-2022-063965
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and their associated factors among patients with cancer receiving treatment at oncology units in Amhara Region, Ethiopia: a cross-sectional study

Abstract: ObjectiveTo assess the prevalence of anxiety and depression symptoms, and their associated factors among patients with cancer receiving cancer treatment in Amhara region oncology centres in Northwest, Ethiopia.DesignInstitution-based cross-sectional study was conducted.SettingThree oncology units at comprehensive hospitals in the Amhara region, Ethiopia.ParticipantsAdult patients who had a pathologically confirmed cancer diagnosis and received cancer therapy were our study participants.Main outcome measuresThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Generally, nine studies assessed the association between age and depression. Of these, five studies indicated that age was not significantly associated with depression ( 16 , 18 , 20 , 29 , 34 ), whereas four studies reported a statistically significant association between age and depression, out of which three of them showed higher risk of depression among younger patients ( 22 , 31 , 33 ), while one study showed higher risk of depression among older cancer patients ( 6 ). This variation between studies might be due to the difference in age categorization and/or sample size across the primary studies.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Generally, nine studies assessed the association between age and depression. Of these, five studies indicated that age was not significantly associated with depression ( 16 , 18 , 20 , 29 , 34 ), whereas four studies reported a statistically significant association between age and depression, out of which three of them showed higher risk of depression among younger patients ( 22 , 31 , 33 ), while one study showed higher risk of depression among older cancer patients ( 6 ). This variation between studies might be due to the difference in age categorization and/or sample size across the primary studies.…”
Section: Resultsmentioning
confidence: 98%
“…Among the 17 studies included in this analysis, one study reported anxiety alone ( 28 ), five studies reported depression alone ( 15 , 16 , 29 31 ), while the remaining 11 studies reported both depression and anxiety ( 6 , 17 , 18 , 20 , 22 , 32 37 ). Correspondingly, the magnitudes of anxiety and depression were determined by pooling findings of 12 ( 6 , 17 , 18 , 20 , 22 , 28 , 32 37 ) and 16 ( 6 , 15 – 18 , 20 , 22 , 29 37 ) studies respectively. All included studies utilized institutional based cross-sectional study design with a sample size ranging from 77 ( 34 ), to 428 ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations